Supramolecular Chirogenesis in a Sterically Hindered Porphyrin: A Critical Theoretical Analysis - Senge, Mathias (My University, 2023)
Invited for the cover of this issue are the groups of Irina Osadchuk at Tallinn University of Technology and Mathias Senge at Trinity College Dublin. The image depicts how a porphyrin with two guest molecules (R)-camphor sulfonic acid is irradiated with UV-visible light to measure and simulate ECD and UV-Vis spectra.